Buckling and post buckling characteristics of laminated composite plates with damage under thermo-mechanical loading. (May 2016) - Sreehari, V.M.; Maiti, D.K.
Abstract: The present work addresses the development of a finite element formulation for handling bending, buckling, and post buckling analysis of composite laminated structures with damage. The inverse hyperbolic shear deformation theory (IHSDT) was applied in the finite element formulation. The effect of damage is analyzed for thin composite plates. An anisotropic damage formulation was used to simulate the damage, which is based on the concept of stiffness reduction. Computer programming is developed in the MATLAB environment. The excellent agreement of the results obtained in the present method with those from references shows that the technique is effective and precise. Parametric studies in the buckling behavior of a damaged composite plate are presented. Critical buckling temperatures are computed for a damaged plate using the present model. Thermal post buckling equilibrium paths are traced for various parametric variations for composite plates with mild damage and compared the results with that of undamaged cases. The validation of IHSDT has been demonstrated for buckling analysis in thermal environment for composite plates with an internal flaw. The present work is worthwhile compared with previous works due to the choice of finite element method and inverse hyperbolic shear deformation theory for analyzing the influence of damage on buckling and post buckling behavior of laminated plates. Highlights: Analysis of buckling and post buckling of composite plates with damage using FEM Governing equations are based on inverse hyperbolic shear deformation theory. Effect of damage is simulated by an anisotropic damage formulation. Critical buckling temperature for a damaged composite plate has been obtained. Effect of mild damage on thermal post buckling paths is presented.